Аналіз стандартів професійного розвитку вчителів американських загальноосвітніх шкіл - Наталія Мукан; Катерина Істоміна (Pavlo Tychyna Uman State Pedagogical University, 2013)
У статті представлено результати наукової розвідки, присвяченої контент-аналізу стандартів професійного розвитку вчителів американських загальноосвітніх шкіл. Досліджено науково-педагогічну літературу, що висвітлює різноманітні аспекти нормативно-правової бази професійного розвитку педагогів. Здійснено ґрунтовний аналіз Стандартів професійного розвитку вчителів американських загальноосвітніх шкіл, розроблених на основі Стандартів професійного розвитку персоналу, а саме Стандартів щодо контексту, Стандартів щодо змісту та Стандартів щодо процесів. Розкрито особливості реалізації стандартів професійного розвитку вчителів на різних рівнях системи неперервної педагогічної освіти у США: індивідуальний рівень, рівень загальноосвітньої школи, рівень органів управління освітою округу, рівень департаменту освіти штату чи зовнішніх провайдерів, федеральний рівень В статье представлены результаты научного исследования, посвященного контент-анализу стандартов профессионального развития учителей американских общеобразовательных школ. Исследовано научно-педагогическую литературу, которая освещает различные аспекты нормативно-правовой базы профессионального развития педагогов. Осуществлен подробный анализ стандартов профессионального развития учителей американских общеобразовательных школ, разработанных на основе стандартов профессионального развития персонала, а именно на основе Стандартов о контексте, Стандартов о содержании и Стандартов о процессах. Представлены особенности реализации стандартов профессионального развития учителей на разных уровнях системы непрерывного педагогического образования США: индивидуальный уровень, уровень общеобразовательной школы, уровень органов управления образованием округа, уровень департамента образования штата или внешних провайдеров, федеральный уровень. In the USA the Standards for Staff Development provide the basis for the elaboration of the standards for professional development of the secondary school teachers in 41 states of the country. These standards were initially created by the National Staff Development Council. They stimulate the development of the positive system of continuing professional education of pedagogues. Nowadays, the optimization of the students' progress is the main focus of the modern educational system. According to this tendency, the evaluation of the students' progress is annually held in the USA, and in case of the unfavorable results the federal government resorts to the presupposed penalties. The Standards of the Professional Development basically fall into three categories: standards of the context of development, standards of the content of development, and standards of the processes of development. The implementation of all these standards in the USA is guaranteed on all the levels of functioning of the educational system starting from the level of each separate individual to the federal level of the state. The main goal of the professional development of the pedagogues is to obtain knowledge, to form skills, which are necessary for various educational needs of the students. It helps the teacher to use different styles, methods, and strategies in their teaching experience, and to organize the better teacher-student interaction model developing the mutual respect and understanding. Compliance with all the standards mentioned above optimizes the process of professional development of the teachers in the secondary schools in the USA, helps to promote a trusty and friendly atmosphere at the work place preparing teachers for the possible conflicts and giving options about how to deal with them. The standards are meant to facilitate the communication within the teachers' community enhancing their team work and communicational skills.